2020
DOI: 10.1007/s11684-020-0787-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of reproduction numbers of COVID-19 in typical countries and epidemic trends under different prevention and control scenarios

Abstract: The coronavirus disease 2019 (COVID-19) has become a life-threatening pandemic. The epidemic trends in different countries vary considerably due to different policy-making and resources mobilization. We calculated basic reproduction number (R 0) and the time-varying estimate of the effective reproductive number (R t) of COVID-19 by using the maximum likelihood method and the sequential Bayesian method, respectively. European and North American countries possessed higher R 0 and unsteady R t fluctuations, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 32 publications
(32 reference statements)
2
38
0
Order By: Relevance
“…Trends with respect to the COVID-19 outbreak varied considerably in each country, primarily because of the different measures taken to promote disease control; these factors included the strictness of these measures, the timing of their implementation, and the resources available. 16,17 In an attempt to prevent or control an outbreak, various government-imposed restrictive measures had been used in different countries. 18 In contrast with Europe and the Americas, a majority of laboratories (135 of 167 laboratories; 80.8%) that responded to our survey reported that the districts in which their laboratories were located had implemented restrictive measures that were strict enough to limit patients' access to health care services.…”
Section: Discussionmentioning
confidence: 99%
“…Trends with respect to the COVID-19 outbreak varied considerably in each country, primarily because of the different measures taken to promote disease control; these factors included the strictness of these measures, the timing of their implementation, and the resources available. 16,17 In an attempt to prevent or control an outbreak, various government-imposed restrictive measures had been used in different countries. 18 In contrast with Europe and the Americas, a majority of laboratories (135 of 167 laboratories; 80.8%) that responded to our survey reported that the districts in which their laboratories were located had implemented restrictive measures that were strict enough to limit patients' access to health care services.…”
Section: Discussionmentioning
confidence: 99%
“…These impacts include school and business closures as well as the ongoing psychological and social tolls of uncertainty, vigilance, and quarantine. In addition to the obvious physical medical impact of this disease [ 3 , 4 ], it poses evident threats to people’s mental health, psychological safety, and well-being [ 5 - 7 ], particularly given the risk of recurrent outbreaks [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the estimated R of the COVID-19 epidemic in these studies is a static value, but R changes dynamically with the prevention and control of the COVID-19 epidemic. Therefore, a time-varying estimate of the effective reproductive number can better quantify the temporal dynamics of the disease 14 , such as the time-dependent reproduction number, which was employed to quantify the temporal dynamics of the disease in African counties and the USA 15 , 16 . Moreover, previous research focused on the R estimation of the overall transmission of COVID-19, but the epidemic trends in different cities vary considerably due to different policy-making and resource mobilization.…”
Section: Introductionmentioning
confidence: 99%